2012
DOI: 10.1093/carcin/bgs184
|View full text |Cite
|
Sign up to set email alerts
|

S -adenosylmethionine decarboxylase overexpression inhibits mouse skin tumor promotion

Abstract: Neoplastic growth is associated with increased polyamine biosynthetic activity and content. Tumor promoter treatment induces the rate-limiting enzymes in polyamine biosynthesis, ornithine decarboxylase (ODC), and S-adenosylmethionine decarboxylase (AdoMetDC), and targeted ODC overexpression is sufficient for tumor promotion in initiated mouse skin. We generated a mouse model with doxycycline (Dox)-regulated AdoMetDC expression to determine the impact of this second rate-limiting enzyme on epithelial carcinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…In contrast, Shi et al demonstrated that a targeted overexpression of AdoMetDC in the skin surprisingly resulted in fewer tumours when compared to control littermates (Ref. 71). A recent study suggests a tumour suppressive role for AdoMetDC by demonstrating that the heterozygous deletion of AdoMetDC and the translational protein eIF5A occur concurrently in human lymphoma and mouse lymphomagenesis (Ref.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, Shi et al demonstrated that a targeted overexpression of AdoMetDC in the skin surprisingly resulted in fewer tumours when compared to control littermates (Ref. 71). A recent study suggests a tumour suppressive role for AdoMetDC by demonstrating that the heterozygous deletion of AdoMetDC and the translational protein eIF5A occur concurrently in human lymphoma and mouse lymphomagenesis (Ref.…”
Section: Introductionmentioning
confidence: 98%
“…A variety of transgenic mice with keratin promoter-driven overexpres-sion of key polyamine regulatory proteins have been used in this mouse skin chemical carcinogenesis model. Although TPA induces two rate-limiting enzymes in polyamine biosynthesis, ODC (O’Brien 1976) and AdoMetDC (Scalabrino et al 1980), overexpression of these enzymes targeted to the skin of transgenic mice results in different effects on tumor development (O’Brien et al 1997; Shi et al 2012). Elevated levels of epidermal ODC are sufficient to promote the development of skin tumors following a variety of initiating events including DMBA (O’Brien et al 1997; Chen et al 2000), UV irradiation (Ahmad et al 2001), and oncogenes (Smith et al 1998; Lan et al 2005) without the use of tumor-promoting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of epidermal ODC are sufficient to promote the development of skin tumors following a variety of initiating events including DMBA (O’Brien et al 1997; Chen et al 2000), UV irradiation (Ahmad et al 2001), and oncogenes (Smith et al 1998; Lan et al 2005) without the use of tumor-promoting agents. In contrast, increased epidermal Ado-MetDC expression is not a sufficient stimulus to drive tumor promotion following DMBA initiation alone (Shi et al 2012). Indeed, increased epidermal AdoMetDC expression suppresses skin tumor promotion in DMBA-initiated/TPA-promoted mice (Shi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamine content is tightly regulated through biosynthesis, catabolism, uptake, and eOEux mechanisms to maintain optimal levels that are required for cellular events such as DNA replication, gene transcription, mRNA translation and ion channel function. Excess polyamine accumulation is linked to neoplastic growth (82). We assayed ODC activity as a measure of potential tumor promoting activity.…”
Section: Attempts At Organ-speciˆc In Vivo Short-term Assays For the mentioning
confidence: 99%